The Effect of Sodium Silicate and Methyl Jasmonate on Pigments and Antioxidant Activity of Tomato (Solanum lycopersicum L.) Under Salinity Stress - Mohammad Javad Arvin (Journal of Agricultural Sciences)
The present study aimed to investigate the effects of sodium silicate (Si) and methyl jasmonate (MeJA) on the pigments and antioxidant activity of tomato, under salinity stress. For this purpose, completely randomized factorial design with three factors including three levels of salinity (0, 4 and 6 dS m-1), Si (0, 4 and 8 mM) and MeJA (0, 5 and 7.5 μM), and three replications was used. The present study displayed that the increase in salinity level reduced chlorophyll index, fluorescence, and vitamin C; however, the catalase (CAT) and ascorbate peroxidase (APX) activities increased. MeJA and Si enhanced the chlorophyll index and vitamin C at different salinity levels, respectively. CAT and APX decreased when the salinized plants were treated with MeJA and Si. MeJA and Si may act to mitigate the adverse effect of salinity stress by reducing the H2O2 production. Finally, it can be concluded that MeJA and Si partially offset the adverse impacts of salinity stress.